Economics of small scale industries - Mohanty, Bedabati. 1942- (New Delhi : Ashish Pub. House, 1986)
Study of Cuttack District based on 1976-1980 data.
Includes index.
Bibliography: p. 214-219.
Keywords: Small business -- India -- Cuttack District